Industrial training report: Mozacrunch International Sdn Bhd / Nur Athirah Md Noh - Md Noh, Nur Athirah (Universiti Teknologi MARA, Perlis, 2023)
To tick off the last list on my bachelor’s degree, I am honoured to carry out my internship as a Sales & Marketing intern at Mozacrunch International Sdn Bhd (Mozacrunch). This report summarises my 24-week experience. Mozacrunch a restaurant that serves flavorful corn sausage. Moza Pop, Moza Crunchy,Moza Cocoyo, Moza Chicky, and Moza Krusty Crab are among the menu options available. I started my internship on March1st, 2023, and finished it on August 15th, 2023. Furthermore, the company entrusted me with the primary responsibilities of joining an event, organising in-person marketing sessions, attending meetings, aiding sales teams in promoting the new product, and engaging with marketing specialists for collaboration and skill growth. At Mozacrunch, I had the opportunity to learn more about marketing and how they run their company. I received a lot of experience through the trainings, meetings,presentations, events, and dealing with customers from varied backgrounds under the supervision of the sales and marketing team. I can say that Mozacrunch is an outstanding eatery since it allows me to learn new things and exposes me to a real work environment and culture. In this report, there is aSWOT analysis as well as some ideas for Mozacrunch to enhance or change for future use.